Promoting reflective thinking in teachers : 44 action strategies - Taggart, Germaine L.; Wilson, Alfred P. (Thousand Oaks, Calif. : Corwin Press, 1998)
Help your teachers ask constructive questions and apply findings from reflective questioning to enhance teacher and student growth and development.
Includes bibliographical references.
Keywords: Teachers -- Training of; Teachers -- In-service training; Thought and thinking; Reflective teaching